2016
DOI: 10.1530/eje-15-1216
|View full text |Cite
|
Sign up to set email alerts
|

Novel calcium-sensing receptor cytoplasmic tail deletion mutation causing autosomal dominant hypocalcemia: molecular and clinical study

Abstract: Objective: Autosomal dominant hypocalcemia (ADH) is a rare disorder caused by activating mutations of the calcium-sensing receptor (CASR). The treatment of ADH patients with 1a-hydroxylated vitamin D derivatives can cause hypercalciuria leading to nephrocalcinosis. Design and methods: We studied a girl who presented with hypoparathyroidism and asymptomatic hypocalcemia at age 2.5 years. Mutations of CASR were investigated by DNA sequencing. Functional analyses of mutant and WT CASRs were done in transiently tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 44 publications
0
8
0
Order By: Relevance
“…Indeed, two ubiquitin ligases, AMSH and dorfin, which reduce CaSR expression by increasing receptor degradation, have been demonstrated to bind to this region of the C-terminus (McCullough et al 2004, Huang et al 2006, and the ADH1 deletion mutants may increase CaSR signalling by reducing receptor degradation. Consistent with this idea, in vitro studies demonstrated that cells expressing the Ser895fsX939 and Ser901-904fsX977 mutants exhibited elevated levels of CaSR protein and increased Ca 2+ i and MAPK signalling when compared to cells expressing WT CaSR (Lienhardt et al 2000, Obermannova et al 2016, Maruca et al 2017. This occurs despite loss of the region identified to bind filamin-A, an actin cytoskeletal protein that enhances CaSR-mediated activation of MAPK pathways (Zhang & Breitwieser 2005).…”
Section: Genetic Landscape Of Adh1mentioning
confidence: 71%
“…Indeed, two ubiquitin ligases, AMSH and dorfin, which reduce CaSR expression by increasing receptor degradation, have been demonstrated to bind to this region of the C-terminus (McCullough et al 2004, Huang et al 2006, and the ADH1 deletion mutants may increase CaSR signalling by reducing receptor degradation. Consistent with this idea, in vitro studies demonstrated that cells expressing the Ser895fsX939 and Ser901-904fsX977 mutants exhibited elevated levels of CaSR protein and increased Ca 2+ i and MAPK signalling when compared to cells expressing WT CaSR (Lienhardt et al 2000, Obermannova et al 2016, Maruca et al 2017. This occurs despite loss of the region identified to bind filamin-A, an actin cytoskeletal protein that enhances CaSR-mediated activation of MAPK pathways (Zhang & Breitwieser 2005).…”
Section: Genetic Landscape Of Adh1mentioning
confidence: 71%
“…There is a tendancy for hypomagnesemia. This syndrome is linked to gain-of-function, or activating, mutations of the CASR gene [4042].

50% of patients present with moderate and asymptomatic hypocalcemia that is found fortuitously,

50% present with paresthesias, tetany, epilepsy, severe hypocalcaemia, sometimes with Bartter syndrome [43],

10% present with hypercalciuria with nephrocalcinosis or lithiasis,

Over 35% present with ectopic and/or basal ganglia calcifications.

…”
Section: Genetic Causesmentioning
confidence: 99%
“…To date, more than 100 germline activating mutations in GPCR genes have been reported (Table and Figure ). Of these, more than 70 were detected in CASR . Patients with GPCR gain‐of‐function mutations manifest inappropriate hormone secretion or function that reflects excessive receptor activity (Table ).…”
Section: Gpcr Mutations and Disordersmentioning
confidence: 99%
“…The N‐terminal domain, the third intracellular loop and the sixth transmembrane domain appear to be hot spots for gain‐of‐function missense mutations (Figure ) . In addition, inframe deletions in CASR and TSHR , as well as frameshift mutations in CASR and PROKR2 have been documented to exert gain‐of‐function effects . Relatively large N‐ and C‐terminal domains of CASR likely provide hot spots for gain‐of‐function mutations (Figure ).…”
Section: Nucleotide Alterations Leading To Gpcr Gain‐of‐functionmentioning
confidence: 99%